2021
DOI: 10.1590/1517-8692202127062021_0059
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Symptoms of Anxiety and Depression Among Medical Students During a Pandemic

Abstract: Introduction: Decreased physical activity has been associated with poorer mental health and is a cause for concern during the COVID-19 pandemic. Objective: To compare groups of medical students (MS) who practiced different levels of moderate and vigorous physical activity (MVPA) during the COVID-19 pandemic, in relation to symptoms of anxiety and depression (BAI-BDI), sleep quality (PSQI), and physical activity (PA) - light, moderate, vigorous (LPA-MPA and VPA), and sedentary behavior (SB). Methods: This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
1
0
7
Order By: Relevance
“…apresentaram qualidade metodológica moderada, 3 (27%) qualidade baixa e apenas 1 (9%) qualidade alta. Todos os estudos utilizaram instrumentos validados (Paixão et al, 2022;Reyes-Molina et al, 2022;Perissotto et al, 2021;Mota et al, 2021;Teixeira et al, 2021;Gonçalves et al, 2021;García-Espinosa et al, 2021;Cavalcanti et al, 2021;Mendes et al, 2021;Saraiva-Bartra et al, 2020) ou adaptados para o contexto do estudo (Hernández-García et al, 2021). Todos os estudos analisaram ao menos dois fatores de confusão (variáveis centrais) em suas análises.…”
Section: Avaliação Da Qualidade Metodológica Dos Estudos Incluídosunclassified
See 2 more Smart Citations
“…apresentaram qualidade metodológica moderada, 3 (27%) qualidade baixa e apenas 1 (9%) qualidade alta. Todos os estudos utilizaram instrumentos validados (Paixão et al, 2022;Reyes-Molina et al, 2022;Perissotto et al, 2021;Mota et al, 2021;Teixeira et al, 2021;Gonçalves et al, 2021;García-Espinosa et al, 2021;Cavalcanti et al, 2021;Mendes et al, 2021;Saraiva-Bartra et al, 2020) ou adaptados para o contexto do estudo (Hernández-García et al, 2021). Todos os estudos analisaram ao menos dois fatores de confusão (variáveis centrais) em suas análises.…”
Section: Avaliação Da Qualidade Metodológica Dos Estudos Incluídosunclassified
“…Apenas os estudos com baixo risco de viés e consequente melhores qualidades metodológicas possuem amostras devidamente representativas e adequadas para avaliação estatística (Teixeira et al, 2021;García-Espinosa et al, 2021;Mendes et al, 2021). Por outro lado, o estudo com mais elevado comprometimento da qualidade metodológica, além de ser formado por amostra não probabilística tomada por conveniência, não faz aplicação adequada de teste estatístico dos dados disponíveis (Cavalcanti et al, 2021).…”
Section: Avaliação Da Qualidade Metodológica Dos Estudos Incluídosunclassified
See 1 more Smart Citation
“…For example, higher levels of PA are associated with lower symptoms of depression and anxiety (Chekroud et al, 2018 ). In this context, it was observed that those individuals who got involved in more moderate–vigorous PA showed fewer symptoms of anxiety and depression (Barcelos-Mendes et al, 2021 ). Méndez-Giménez et al ( 2021 ) also discovered that volume (METs-min/week), frequency (days/week), and volume (hours) of PA were inversely associated with the likelihood of developing depressive symptoms during home confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos como o deMendes et al (2021) eDang et al (2021) destacam que a prática regular e constante de atividade física associada a uma dieta balanceada está associada a uma diminuição significativa nos sintomas depressivos, com resultados consistentes em diferentes populações e contextos.…”
unclassified